Aluminum-induced oxidative stress promotes changes in the structure of the gut microbiota and liver deficiency - Rong Feng; Liang Chen; Ming Yang (Heliyon, 2024)
As a low-toxicity metal, aluminum has garnered increasing attention in relation to its impact on the human body; however, the specific mechanism of action remains unclear. To bridge this knowledge gap and facilitate practical applications, this study took 8-week-old ICR mice as the research object to study the effects of dietary addition of aluminum potassium sulfate on intestinal flora structure and liver. As the concentration of aluminum increased, it inhibited mice weight growth rate and significantly altered the composition of white blood cells in their bloodstream. Histological examination revealed liver inflammation through HE staining sections. The oxidative stress markers MDA increased, GSH-PX and CAT decreased significantly. And liver function index MAO increased, TC and ALP decreased first and then increased. Moreover, there was a significant increase in pro-inflammatory factor TNF-α content. Further 16S rRNA sequencing analysis demonstrated substantial changes in both composition and structure of mouse intestinal microbiota induced by aluminum exposure; microbial phenotype prediction indicated that aluminum-induced oxidative stress promoted an increase in abundance of oxidation-resistant microbial types. Alterations in gut flora structure also influenced the liver via the gut-liver axis. These findings lay a foundation for further research on the regulation and interaction of aluminum on intestinal flora.